2021
DOI: 10.5812/jjnpp.112653
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Hepatoprotective Activity of the Curcuma heyneana Rhizome Extract toward Wistar Rats Induced by Ethanol

Abstract: Background: Curcuma heyneana (Valeton & Zijp.) or temu giring has various pharmacological activities. However, its hepatoprotective activity toward ethanol induction has never been carried out. Objectives: The objective of this research was to evaluate the hepatoprotective activity of the C. heyneana rhizome extract toward Wistar rats induced by ethanol. Methods: The research was initiated with the determination of curcuminoid content, total phenolic content, total flavonoid content, and characterization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Temu giring (Curcuma heyneana) is one of the native plants of Indonesia (Sugita et al 2018) which contains phenolic and flavonoid compounds in its rhizome (Marianne et al 2021). Previous studies have documented the ability of these secondary metabolites to convert silver ions into elemental silver (Dauthal and Mukhopadhyay 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temu giring (Curcuma heyneana) is one of the native plants of Indonesia (Sugita et al 2018) which contains phenolic and flavonoid compounds in its rhizome (Marianne et al 2021). Previous studies have documented the ability of these secondary metabolites to convert silver ions into elemental silver (Dauthal and Mukhopadhyay 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These plants turned out to have potential as herbal plants that can be used to overcome health problems. Temu giring (Curcuma heyneana) is one of the native plants of Indonesia (Sugita et al 2018) which contains good phenolic and flavonoid compounds in its rhizome (Marianne et al 2021). However, no one has used this plant for the synthesis of silver nanoparticles, so this research aims to do so.…”
Section: Journal Of Biosciences Journal Of Biosciencesmentioning
confidence: 99%
“…Natural antioxidants work systemically and possess the ability to prevent aging in cells and tissues [ 14 ]. Examples of plants that meet these criteria include those from the Zingiberaceae family, such as C. heyneana and C. longa , which demonstrate antioxidant and anti-aging activities [ 68 , 69 ]. It can be seen that many SAD people use turmeric as a body scrub which is applied to the body at traditional wedding events for women, so that it can be developed into a new anti-aging potential from the curcumin compound contained in C. longa .…”
Section: Herbs With Anti-aging Propertiesmentioning
confidence: 99%
“…Based on the research conducted by Marianne et al (2021) and Zeeshan et al (2018), it has been found that the plant C. heyneana contains phytochemical compounds such as curcumin and demethoxycurcumin, which act as antioxidants [ 68 , 69 ]. In a study by Rohman et al (2020), the antioxidant activity of curcumin extracted from C. heyneana was evaluated using the DPPH method, and it exhibited a strong antioxidant capacity with an IC 50 value of 62.5 µg/mL [ 70 ].…”
Section: Herbs With Anti-aging Propertiesmentioning
confidence: 99%
See 1 more Smart Citation